Influence of Eating Habits on Nutritional Status among Basic Level Students in Nepalgunj - Acharya, Lal Mani (Academia Research Journal, 2026)
This field-based study examines eating habits and their impact on the nutritional status of 125 basic level students (classes 1-8) from four schools in Nepalgunj, Banke: Mangal Prasad Secondary School, Dhambojhi Secondary School, Saraswati Secondary School, and Narayan Secondary School. Objectives include assessing eating habits and nutritional knowledge, and identifying malnutrition conditions. Data were collected via simple random sampling, interviews, observations, and anthropometric measurements (height, weight, MUAC, BMI). Results indicate a sex ratio of 86.56, with 96% Hindu population and 43.2% Tharu ethnicity. Parental education peaks at SLC (23.2%), and agriculture is the primary occupation (43.2%). Notably, 76.8% prefer junk food over home-made (23.2%), yet 80% exhibit normal nutrition, 16% mild malnutrition, and 4% moderate. All students are immunized, but 13.6% lack tiffin lunch, highlighting parental nutrition awareness gaps. Anthropometric analysis shows 74.4% normal height-for-age, 21.6% moderate stunting, and 4% acute stunting. Findings advocate for school-based awareness programs and balanced diets to enhance child health in rural Nepali contexts.